Characterization of Yellow Tabebuia Flower Extract (Tabebuia Aurea) Nanoparticles - Yunita Yunita; Anisa Lailatusy Syarifah; Lina Oktavia Rahayu; Ernanin Dyah Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Degenerative diseases can be prevented by natural antioxidants in plant. Yellow tabebuia flower is the natural antioxidants. Plant extracts can be developed into green synthesis nanoparticle to increase the effectiveness as medicinal materials. This research aims to determine the characteristics of yellow tabebuia flower extract nanoparticles and bioactivity as antioxidants. The methods included preparation and extraction of simplisia using ethanol solvent by maceration and sonication methods. The extract was determined flavonoid and phenol content by colorimetric method and antioxidant activity by DPPH method. The extract was also made into nano particles by ionic gelation method, with variations in the addition of tween 80 as much as 0.5, 0.75 and 1 ml. The results of this research are extract has a yield 13.09%, contains flavonoids, tannins, phenolics, alkaloids, saponins and terpenoids/steroids. The use of ionic gelation method can reducing particle size. Three formulas made the variation of surfactant addition has a particle size of 47-283 nm, in addition tween 80 1 ml has the smallest particle size of 47 nm with a zeta potential value of 39.3 mV.